The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s0033291707002024
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of borderline personality disorder features is similar across three countries

Abstract: Background. Most of our knowledge about borderline personality disorder features has been obtained through the study of clinical samples. Although these studies are important in their own right, they are limited in their ability to address certain important epidemiological and aetiological questions such as the degree to which there is a genetic influence on the manifestation of borderline personality disorder features. Though family history studies of borderline personality disorder indicate genetic influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
143
2
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(169 citation statements)
references
References 80 publications
19
143
2
5
Order By: Relevance
“…Since earlier analyses showed that women have higher BPT scores than men (Distel et al, 2008), scores were adjusted for sex before the genetic analyses using linear regression. Figure 1 shows the bivariate genetic model.…”
Section: Genetic Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Since earlier analyses showed that women have higher BPT scores than men (Distel et al, 2008), scores were adjusted for sex before the genetic analyses using linear regression. Figure 1 shows the bivariate genetic model.…”
Section: Genetic Modelingmentioning
confidence: 99%
“…The resemblance within and between relatives across BPT and the liability for substance use variables was also summarized with Pearson product-moment correlations. Since earlier analyses showed that women have higher BPT scores than men (Distel et al, 2008), scores were adjusted for sex before the genetic analyses using linear regression. Figure 1 shows the bivariate genetic model.…”
Section: Genetic Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has demonstrated, however, that each of these factors interacts in multiple ways to shape the development and course of BPD. For example, some studies have reported that individuals with BPD are five times more likely than by chance alone to have a first-degree relative with BPD, 42 implicating the notion of heritability, and a recent twin study demonstrated that genetic influences explain 42% of the variance in BPD symptoms. 42 Other studies have also implicated a biological involvement.…”
Section: Complex Ptsd: the Phenomenological Overlap With Bpd Symptomamentioning
confidence: 99%